Media Sosial Dalam Pengembangan Ekowisata di Kawasan Wisata Pesisir Rawan Bencana Kabupaten Cilacap - Ahdiati, Triana; Soebiantoro, M.; Kusumanegara, Solahuddin (Jurnal Ilmiah Pariwisata, 2022)
This research aims at describing social media in the ecotourism development in disaster-prone coastal tourism area, Cilacap Regency, especially in Widarapayung Wetan Village. By using a qualitative method through an action research approach, the result of the research indicates that social media is needed for developing ecotourism in that area. Apart from being a means of tourism promotion, social media is also an effective means of supporting the implementation of disaster risk reduction programs in the region. Due to the limited resources available, however, the development of ecotourism through the use of blog as social media still needs to be done gradually and sustainably. In addition, a comparative study to tourist areas in other regions also shows that the development of the ecotourism blog by Pokdarwis PIW is very significant to increase the capacity of disaster-prone coastal communities in the area. Keywords: Ecotourism, Social Media, Blog, Disaster-Prone Coastal Tourism Area